KOORDINASI PADA PROSES PENYIDIKAN ORANG ASING YANG MELAKUKAN TINDAK PIDANA KEIMIGRASIAN BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN PADA KANTOR IMIGRASI KELAS I SEMARANG - Aldi Subartono; Suhaidi Suhaidi; Mahmul Siregar; Mahmud Mulyadi (USU LAW JOURNAL, 2014)
ABSTRAK Law No. 6 of 2011, include the presence of civil servant investigators, which is provided for in Article 105, which confirms that immigration investigators are authorized as a criminal offense Immigration investigators conducted in accordance with the provisions of this Act. Meanwhile, in Article 107 it is explained that in conducting an investigation, criminal offense Immigration investigators must coordinate with Indonesian police officer  to prevent misleading in the investigation.  Investigation process to Foreigners by Law No. 6 of 2011 on Immigration in accordance with Article 105 where investigators Immigration is authorized as a criminal offense Immigration investigators. Semarang First class Immigration Office investigators in 2013 has been investigating 9 immigration and criminal cases. They have sent 3 cases to the public prosecutor in the State Attorney Semarang.  The Coordination between first class Immigration Office investigators and Korwas PPNS Central Java Police’s special criminal unit doesn’t went according to the present law. This condition is caused by Semarang first Class Immigration Office investigators did not give written notice of the commencement and the result of the investigation and to provide a copy of the case to Korwas PPNS. Keywords : Coordination, Immigration Crime, Investigation